2017
DOI: 10.1159/000477168
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes of Non-Primary Maternal Cytomegalovirus Infection: A 15-Year Experience

Abstract: Objective: To evaluate perinatal outcomes in case of non-primary maternal cytomegalovirus (CMV) infection. Methods: We performed a retrospective cohort study of pregnant women with active CMV infection referred to our unit over a 15-year period (January 2000 to December 2014). Non-primary infection was diagnosed on the basis of the results of confirmatory serological and virological tests (avidity test, immunoblotting, real-time PCR-DNA). The vertical transmission rate and the percentage of symptomatic congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…Prospective studies showed that maternal immunity is protective against congenital HCMV infection, with highly significantly reduced rates of vertical transmission in women with nonprimary compared to primary infections. 125,126 Primary infections result in HCMV transmission in approximately 30% of affected pregnancies, whereas preexisting maternal immunity confers a 69% reduction of the risk of congenital HCMV in future pregnancies. 127,128 Moreover, there is evidence that sequelae of congenital HCMV infection are reduced in the setting of preconception maternal immunity.…”
Section: Rna Hcmv Vaccinesmentioning
confidence: 99%
“…Prospective studies showed that maternal immunity is protective against congenital HCMV infection, with highly significantly reduced rates of vertical transmission in women with nonprimary compared to primary infections. 125,126 Primary infections result in HCMV transmission in approximately 30% of affected pregnancies, whereas preexisting maternal immunity confers a 69% reduction of the risk of congenital HCMV in future pregnancies. 127,128 Moreover, there is evidence that sequelae of congenital HCMV infection are reduced in the setting of preconception maternal immunity.…”
Section: Rna Hcmv Vaccinesmentioning
confidence: 99%
“…Thus, although prior maternal infection with CMV does not provide complete protection against transmission to the fetus, it does clearly reduce the risk. Indeed, two recent prospective studies both indicated a protective effect of maternal immunity against congenital CMV infection, with highly significantly reduced rates of vertical transmission in women with nonprimary compared to primary infections (31,32). Thus, although imperfect, there is evidence to support the contention that preconception maternal immunity to CMV is a barrier to vertical transmission.…”
Section: Correlates Of Protective Maternal Immunity and Potential Formentioning
confidence: 99%
“…Recent studies show that seropositive mothers have high rates of reinfection with new virologic strains of CMV, ranging from 18-30% [13,14], suggesting that reinfection could be a major mode of non-primary cCMV infection. Birth prevalence of non-primary cCMV infection among infants born to all seropositive women is estimated to be 1%, yet placental transmission has been reported to be as high as 3.4% in women who have evidence of reinfection during pregnancy [8,15]. Seronegative mothers residing in areas of low CMV seroprevalence have low rates of maternal CMV acquisition ranging from 1-3% [1], yet placental CMV transmission rates in these cases of primary maternal CMV infection during pregnancy range from 30-50% [16][17][18].…”
mentioning
confidence: 99%